Pembelajaran Praktek Tari melalui Daring (dalam Jaringan) pada Masa Pandemi Covid-19 - Dinny Devi Triana; Rahmida Setiawati; Sudirman, Natasha (Jurnal Pendidikan Tari, 2023)
This study aims to find out how to learn Balinese dance practices through online learning. The method used in this research is descriptive qualitative. Data collection techniques are carried out by means of observation, interviews, and documentation. The results of this study are learning Balinese dance practices during the Covid-19 pandemic in the Dance Education Study Program, Faculty of Languages and Arts, Jakarta State University using the teacher centered learning method. The special Balinese dance learning methods used by lecturers are moguru ear, moguru mata/mate, moguru nuutin, moguru crew, and moguru me silehkrame. The learning media used are WhatsApp groups, zoom meetings, and Google Drive. As for the factors that hinder the process of learning Balinese dance practices, the most common are signal problems and limited quotas. Apart from that, there were also several obstacles experienced by students, such as devices that did not support online learning, and many students found it difficult to analyze movement techniques through online learning. The evaluation was carried out in the Balinese dance course, namely students were asked to make dance videos and make videos of motion techniques in the Leggong dance, the assessment made emphasized the process rather than the final result.